The efficiency of Colombian hospitals in the Latin American context. An application of Data Envelopment Analysis (DEA) in a group of complex surgeries hospitals, 2009 (2020)
The medical services of complex surgeries is a sector with high potential for generating foreign exchange and it owns a good competitive performance due the access to high technology developments. The measurement of efficiency in this sector in the country is an important aspect, if we want to be competitive. In a sample of 20 Latin American hospitals, was measured the efficiency of the group of 5 Colombian entities included there. The measurement was made by the DEA methodology. The results showed that 4 of the Colombian institutions are on the efficient frontier and the remaining one must make adjustments in the use of physical space in those areas where this is possible. The combination of efficiency, competitive prices and quality service, augur a good future for medical services of complex surgeries in Colombia.